An Evaluation on Means to upgrade the Effectiveness of Judiciary in Pakistan: A Content Based Overview - Dr. Hamida (Journal of Peace, Development and Communication, 2022)
This study is an endeavor to explore the major barricades as faced by the Judiciary of Pakistan while rendering the service delivery to the aggrieved parties in society and to evaluate the effectiveness of judiciary while rendering its deliverance of service mainly through analyzing the contents available in literature. The study is done mostly on the principles of mix methodology. Primary and secondary sources have been critically analyzed to understand and different hurdles as in the way of its effective performance. Modern tactical, scientific and substantial measures has been recommended for upgrading dexterous approach and to improve its efficacy and meagerness.